2009
DOI: 10.1016/j.vaccine.2009.03.069
|View full text |Cite
|
Sign up to set email alerts
|

The mast cell activator compound 48/80 is safe and effective when used as an adjuvant for intradermal immunization with Bacillus anthracis protective antigen

Abstract: We evaluated the safety and efficacy of the mast cell activator compound 48/80 (C48/80) when used as an adjuvant delivered intradermally (ID) with recombinant anthrax protective antigen (rPA) in comparison with two well-known adjuvants. Mice were vaccinated in the ear pinnae with rPA or rPA + C48/80, CpG oligodeoxynucleotides (CpG), or cholera toxin (CT). All adjuvants induced similar increases in serum anti-rPA IgG and lethal toxin neutralizing antibodies. C48/80 induced a balanced cytokine production (Th1/Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
71
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 75 publications
(72 citation statements)
references
References 71 publications
0
71
1
Order By: Relevance
“…More recently, however, the importance of mast cells as initiators and effectors of innate immunity as well as their potential role in influencing adaptive immune responses have been appreciated (1,2). Granule products from mast cell degranulation, triggered by secretagogues, were demonstrated to facilitate humoral immune responses (3,4). These studies investigated the efficacy of s.c., intranasal (i.n.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, however, the importance of mast cells as initiators and effectors of innate immunity as well as their potential role in influencing adaptive immune responses have been appreciated (1,2). Granule products from mast cell degranulation, triggered by secretagogues, were demonstrated to facilitate humoral immune responses (3,4). These studies investigated the efficacy of s.c., intranasal (i.n.…”
mentioning
confidence: 99%
“…TNF-a stimulated recruitment of dendritic cells (DCs) and lymphocytes to draining lymph nodes. Collectively, these observations have elegantly identified the mast cell as a potential regulator of the adaptive immune response (3,4). Thus, mast cell activators have been proposed to be a new class of immunomodulators, capable of adjuvanting protective immunity following mucosal vaccine administration.…”
mentioning
confidence: 99%
“…Furthermore, McGowen et al reported that C48/80 produced much greater levels of IFN than it did IL-4, IL-5, IL-6 or IL-17, and reduced the IgG1/IgG2a ratio. Therefore they considered it possible that C48/80 acts through the connective tissue mast cells to stimulate an environment favorable for the development of Th1 immune responses (15). Based on the above, synergy may be created by the combined treatment of C48/80 and local hyperthermia, which form an effective resistance to lung metastasis in the therapy for lung metastasis treatment.…”
Section: Discussionmentioning
confidence: 99%
“…RNA was prepared by homogenization of the tumor with RNAzol followed by RNA extraction according to the manufacturer's instructions. RNA concentrations were measured, and 2 µg total cellular RNA was reverse transcribed in a 200-µl volume using oligo(dT) 15 as a primer and Moloney murine leukemia virus reverse transcriptase. cDNA (2 µl) was amplified by PCR using primers specific to individual murine cytokines.…”
Section: Detection Of Cytokine Mrna In the Spleen Using Rt-pcrmentioning
confidence: 99%
“…This anti-Vi standard was assigned an arbitrary anti-Vi IgG value of 200 ELISA units (EU) per ml. For comparison of the Vi bead assay to ELISA, we utilized an ELISA protocol similar to what we have previously reported (6,(28)(29)(30) with modifications as described below. Vi polysaccharide (1.0 g/ml) was diluted in CBC coating buffer (pH 9.5; 15 mM Na 2 CO 3 and 35 mM NaHCO 3 ) before adding 15 l to each well of a 384-well black Nunc Maxisorp plate (catalog no.…”
Section: Methodsmentioning
confidence: 99%